ANALISIS STRATEGI PENGEMBANGAN SEKTOR EKONOMI KABUPATEN BOLAANG MONGONDOW TIMUR - Paputungan, Dwi R.; Amo, Farisa Maulinam (Universitas Muhammadiyah Gorontalo, 2025)
Economic growth is now a benchmark for regional development. High regional economic growth will ensure the prosperity of the people living in the area. The economic growth of East Bolaang Mongondow Regency grows every year but has slowed down due to the lack of maximization of other sectors besides mining and agriculture. The research was conducted to identify the basic sectors or areas favored by East Bolaang Mongondow Regency, as well as to determine the most effective strategy to increase the existing economic potential. The research was conducted using quantitative methods with a descriptive approach. For analysis techniques, researchers used LQ analysis, Shift Share analysis, and SWOT analysis. The results of the study show that there are 3 basic or leading sectors in East Bolaang Mongondow Regency, these three sectors contribute the most each year compared to other sectors. To encourage economic growth, the government must take more initiative in optimizing the potential of the region by implementing better development programs in accordance with regional conditions, so that the leading sectors can encourage the development of non leading sectors